A Holistic Approach to Cybersecurity and Data Protection in the Age of Artificial Intelligence and Big Data - Karpiuk, Mirosław; Melchior, Claudio; Kaczmarek, Krzysztof (PRAWO i WIĘŹ, 2024)
With rapid technological advances, cybersecurity and personal data protection are becoming key issues that require a holistic approach. The dynamic development of artificial intelligence (AI) and big data technologies creates new opportunities for cybersecurity. At the same time, potential attack vectors are emerging. The paper highlights the relationship between cybersecurity and the protection of personal data, and points to the need for integrated action at several levels. These include the development and implementation of advanced technological solutions and education to increase users’ digital literacy. The analysis shows that only by balancing the potential of modern technologies with the risks associated with the human factor is it possible to effectively protect personal data in the digital ecosystem.